Sutureless and Glue Free Conjunctival Autograft in Pterygium Surgery - Uzma Taqi; Erum Shahid (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2022)
Objective: The objective of the study is to report a newer technique of pterygium excision followed by suture less and glue free conjunctival autograft for its complications and recurrence rate.